A Reexamination of Accountants' Organizational-Professional Conflict. - Aranya, Nissim; Ferris, Kenneth R. (The Accounting Review, 1984)
Abstract ABSTRACT: This study analyzes the antecedents and outcomes of the organizational-professional conflict of accountants working in government, industry, and the profession. Hypotheses were generated and examined for a sample of 2,016 U.S. and Canadian accountants. The findings indicated that: (1) the organizational-professional conflict of accountants working in professional organizations was lower than that of accountants employed in nonprofessional organizations; (2) within professional organizations, ,the level of perceived conflict varied inversely with position in the hierarchy; and (3) the perception of conflict was negatively related to job satisfaction and positively related to employee turnover intentions.